An inquiry into changes in everyday bicycling cultures: the case of Johannesburg in conversation with Amsterdam, Beijing and Chicago - Morgan, Njogu (My University, 2017)
This thesis examines shifts in the everyday use of bicycles in the different contexts that are the subject of this study. In doing so it explores how associated symbolic meanings are produced and reproduced and shape everyday cycling. While many studies have shown how meanings and other cultural attributes influence cycling, there has been insufficient focus into their formation in the cycling literature leading to calls for greater understanding into their formation. Other studies shedding light into production processes reside in different scholarly traditions, limiting the possibility of interdisciplinary learning. Understanding how meanings are produced and the role of context in particular, responds to queries in the cycling literature. It can also support context sensitive policy solutions to promote bicycling for transport. To explore these questions and objectives, a historical comparative study into the changing use of bicycles for everyday purposes in Johannesburg, Amsterdam, Beijing and Chicago is undertaken. Using a framework of analysis from transitions theory, the thesis argues that meanings emerge and change through a dynamic interrelated process involving actor activities in building or unravelling a bicycling socio-technical system and alternative ground transport solutions, contextual characteristics and associated changes, and cycling experiences. In these processes, (in)equalities in social relations resident in contexts play an important role in the production of meaning. Moreover, as meanings emerge, they do so together with user practices, technology, infrastructures, social norms, and other elements that constitute transport systems. Since there are multiple co-interacting factors that produce meanings about bicycling, policy efforts could with advantage pay attention to these and in particular how they assume specificities in contexts. The thesis also breaks ground by offering a novel empirical history of everyday cycling in Johannesburg.
A thesis submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy, Johannesburg October 2017
Keywords: Cycling--Social aspects; Bicycles